The Seneca restoration, 1715-1754 : an Iroquois local political economy - Jordan, Kurt A., 1966- (University Press of Florida, 2008)
The Iroquois nation is commonly perceived as having plunged into a steep decline in the late 17th century due to colonial encroachment into the Great Lakes region. This book challenges long-standing interpretations that depict the Iroquois as defeated, colonized peoples.